Variability of EEG‐fMRI findings in patients with SCN1A‐positive Dravet syndrome. Issue 5 (8th February 2013) - Moehring, Jan; von Spiczak, Sarah; Moeller, Friederike; Helbig, Ingo; Wolff, Stephan; Jansen, Olav; Muhle, Hiltrud; Boor, Rainer; Stephani, Ulrich; Siniatchkin, Michael
Summary Purpose Dravet syndrome (DS) or severe myoclonic epilepsy of infancy is an intractable epileptic encephalopathy of early childhood that is caused by a mutation in the SCN1A gene in most patients. The aim of this study was to identify a syndrome‐specific epileptic network underlying interictal epileptiform discharges (IEDs) in patients with DS. Methods Ten patients with the diagnosis of DS associated with mutations in the SCN1A gene were investigated using simultaneous recording of electroencephalography and functional magnetic resonance imaging ((EEG‐fMRI). Time series of IEDs were used as regressors for the statistical fMRI analysis. Key Findings In nine patients with DS, individual blood oxygenation level–dependent (BOLD) signal changes were seen. In three patients the thalamus was involved. Furthermore, regions of the default mode network were activated in seven patients. However, a common activation pattern associated with IEDs could not be detected. Significance The study demonstrates that, despite a common genetic etiology in DS, different neuronal networks underlie the individual IEDs.